2020
DOI: 10.1021/acsearthspacechem.9b00321
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Quantum Chemistry Study of Neutral and Charged C4N Chains: An Attempt To Aid Astronomical Observations

Abstract: Many molecular species can presumably still be observed in space if they are adequately characterized chemically. In this paper, we suggest that this could be the case of the neutral (C 4 N 0 ) and anion (C 4 N -) cyanopropynylidene chains, which were not yet identified in space although both the neutral (C 3 N 0 and C 5 N 0 ) and anion (C 3 Nand C 5 N -) neighboring members of the homologous series were observed. Extensive data obtained from quantum chemical calculations using density functional theory (DFT),… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 77 publications
(173 reference statements)
0
10
0
Order By: Relevance
“…Insight gained in conjunction with our recent investigations of astrochemically relevant carbon chain anions [ 26 , 27 , 28 , 29 ] made us skeptical that shorter HC n H − anion chains possess a stable linear geometry, as claimed earlier [ 23 ]. Our extensive attempts to optimize HC n H − anions imposing strict linear conformation confirmed previous results reported for sizes [ 24 , 25 ]; we also found that irrespective whether n is odd or even, such sufficiently long HC n H − anions, linear and invariant under spatial inversion, are stable against molecular vibrations, i.e., all calculated frequencies were real.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Insight gained in conjunction with our recent investigations of astrochemically relevant carbon chain anions [ 26 , 27 , 28 , 29 ] made us skeptical that shorter HC n H − anion chains possess a stable linear geometry, as claimed earlier [ 23 ]. Our extensive attempts to optimize HC n H − anions imposing strict linear conformation confirmed previous results reported for sizes [ 24 , 25 ]; we also found that irrespective whether n is odd or even, such sufficiently long HC n H − anions, linear and invariant under spatial inversion, are stable against molecular vibrations, i.e., all calculated frequencies were real.…”
Section: Resultsmentioning
confidence: 95%
“…Still, are all HC n H − chains with molecular sizes of astrochemical interest really linear and centrosymmetric? This was the fundamental question that triggered the investigation whose results will be presented below, and emphasizing anions is part of our recent [ 26 , 27 , 28 , 29 , 30 ] and ongoing effort to understand their role in astrochemistry, which is claimed to even compete with that of the parent neutrals [ 29 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 48–51 ] A variety of carbon‐based anion chains were investigated in the past [ 26,49,50,52–57 ] also using elaborate ab initio quantum chemical methods beyond the DFT. [ 51,58–60 ] As far as the HC n H family is concerned, previous studies only reported values of EA estimated via Δ‐DFT [ 46,61,62 ] for even members HC 2 k H with 6k12$ 6 \le k \le 12$ [ 37 ] and 2k6$ 2 \le k \le 6$, [ 45 ] and for odd members HC2k+1$_{2k+1}$H with 4k11$ 4 \le k \le 11$. [ 38 ] However, one may wonder whether DFT‐based EA values are accurate enough for reliable modeling the chemical evolution in extraterrestrial environments.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our study emphasize that, while important, e.g., for modeling the temporal evolution of various molecular species interacting among themselves in a given chemical environment [ 65 , 67 ], the global chemical reactivity indices have no direct relevance for antioxidation. Recall that we saw in Section 3.2 that quantitative differences of ATV’s o-ATV’s, and p-ATV’s global chemical reactivity indices are minor.…”
Section: Discussionmentioning
confidence: 99%